Japan's Finacial crisis : - Amyx, Jennifer Ann (Princeton University Press, 2004)
The book focuses on the role of policy networks in Japanese finance, showing with nuance and detail how Japan's Finance Ministry was embedded within the political and financial worlds, how that structure was similar to and different from that of its counterparts in other countries, and how the distinctive nature of Japan's institutional arrangements affected the capacity of the government to manage change.